From Peasant to Petersburger - Economakis, E. author. aut Link
XI, 212 p.
Keywords: Economakis analyses the processes of proletarianization and urbanization undergone by St. Petersburg's industrial working class from its inception in the early nineteenth century up until 1914. Attention is given to the severing of workers' ties to the village and the land. The book examines local conditions in sending areas and traces the history of factory work in St. Petersburg by workers from different provinces. Economakis finds that a majority of the factory workforce was objectively proletarianized by 1914.